057 Has a pay for performance strategy in primary care improved epilepsy management in the UK?. Issue 3 (9th February 2012) - Glasbey, J C D; Gilpin, T R; Steer, S; Thomas, R H; Smith, P E M
Abstract : Introduction: The New GP Contract (2004) introduced reward for achievement in quality of organisation and disease management. We investigated how a pay for performance strategy has affected epilepsy care as measured by the quality and outcomes framework (QOF). Method: Using QOF datasets from 2005 and 2010, we analysed patterns of epilepsy QOF point attainment for individual LHBs/PCTs. We then compared the percentage of QOF points obtained for epilepsy with percentage gained for other chronic diseases (heart failure, asthma, diabetes) to determine which diseases' management are 'prioritised' by GPs. Results: In Wales QOF attainment has significantly risen since 2005 (p<0.0001). Mean QOF attainment has risen from 94% (min 67.9%, max 100%) to 98% (min 84.5%, max 100%). However in England most areas saw a decrease in QOF points obtained (p<0.0001). Motivated GPs in resource poor settings such as Blaenau Gwent (+26.03%), and Rhondda Cynon Taf (+23.63%) demonstrated the greatest improvement despite still having some of the lowest scores in Wales. Epilepsy QOF scores were lower than scores for other chronic diseases e.g. heart failure in Wales (p=0.00012), despite a similarity in prevalence and QOF points available. Conclusions: QOF can be demonstrated to motivate GPs to prioritise epilepsy care in practices which initially scored poorly. However it is a concern that QOF point attainment is also seen to drop in areas that had previously scored well. This may represent 'gamesmanship' from GP practices as they focus on conditions which are easiest to score well on—or conversely that the QOF targets for epilepsy are reassuringly difficult to attain.